Metamorphic mineral assemblages south of the Malakand and adjoining areas, northern Pakistan - Ahmad, Irshad; Jan, M. Qasim; Jehan, Noor (Journal of Himalayan Earth Sciences, 2005)
The mineral assemblages (calcite + muscovite + hornblende + quartz + plagioclase + zoisite + garnet) indicate epidote amphibolite facies conditions in the north near Mora Kandao south of the Malakand, north Pakistan. With the reported occasional occurrence of kyanite indicate that the metamorphism is probably of the medium pressure i.e., Barrovian type. Based on the mineral assemblages, temperatures of 580oC are assumed for the epidote amphibolite facies and pressures about 5.5 kb in the north. The greenschist facies rocks in the south near Takht-e-Bhai, Rustam and surrounding, the mineral assemblage actinolite + biotite + muscovite + quartz + albite + magnetite and color index of conodont 5.5 to 7 suggesting peak metamorphic temperatures between 300 and 400oC and pressures up to 3 kb. Temperature and pressure for the melange blocks and matrix are assumed between 200 and 570oC with pressure 3 kbar.